Maritime-oriented foragers during the Late Pleistocene on the eastern costa del sol (Southeast Iberia): Cueva Victoria (Málaga, Spain) - Esteban Álvarez-Fernández; J. Emili Aura Tortosa; Jesús F. Jordá Pardo; Ismael Palomero-Jiménez; Mª Teresa Aparicio; Lidia Cabello-Ligero; Pedro Cantalejo; Margarita Vadillo Conesa; Yolanda Carrión Marco; María del Mar Espejo; Mª José Fernández-Gómez; Naroa García-Ibaibarriaga; et al. (Heliyon, 2022)
The Mediterranean coast of Spain is marked by several clusters of Palaeolithic sites: to the south of the Pyrenees, in the area around the Ebro River, in the central part, and on the south coast, one of the southernmost regions in Europe. The number of sites is small compared with northern Iberia, but like that region, the Palaeolithic occupations are accompanied by several rock art ensembles. The archaeological material (both biotic and abiotic resources) and radiocarbon dates presented here were obtained during archaeological fieldwork of professor J. Fortea in the Late Pleistocene deposits in Cueva Victoria, located near the modern coastline and about 150 km north of the Strait of Gibraltar. In the three occupation phases, marine resources were acquired by shell-fishing (focusing almost exclusively on the clam Ruditapes decussatus), fishing, and the use of beached marine mammals. This contrasts with the limited data about the exploitation of terrestrial resources by hunting and gathering animals and plants. The study is completed by the study of artefacts (lithic and bone industry and objects of adornment) that help to understand the subsistence strategies of the cave occupants and enable a comparison with other groups inhabiting the Mediterranean coasts of the Iberian Peninsula during Greenland Interstadial 1, between ca. 15.1 and 13.6 cal BP.